Silk proteins and its biomedical and dental application: A Review: Silk proteins in medical and dental field - Devi, Devarathnamma MV; Bhat, Geeta; Bhat, Manohar; Sharma, Deepak; Rangappa, Janavathi (International Journal of Clinical and Biomedical Research, 2022)
Silk is a group of fibrous proteins that have been used for centuries in the textile industry and as surgical sutures. Silk, in addition to its unique mechanical properties, silk possesses other properties, such as biocompatibility, biodegradability, anti-bacterial properties, thermal stability, controlled degradation features, and ease of sterilization, ability to self-assemble make it a promising material for biomedical applications. Although silk forms only fibers in nature, synthetic techniques can be used to control the processing of silk into different morphologies, such as scaffolds, films, hydrogels, microcapsules, and micro- and nanospheres. Moreover, the biotechnological production of silk proteins broadens the potential applications of silk. With this background, this review describes silk proteins, their properties, synthesis, and uses. Keywords: Silk, Silk proteins, Sericin, Fibroin, Dental